Systems thinking: embedding closure planning within the management operating system is the key to drive closure performance - Lacy, H.W.B.; Slight, M.; Watson, A. (Mine Closure 2019: Proceedings of the 13th International Conference on Mine Closure, 2019)
Miners worldwide are making large investments in innovation with a view to developing safe, efficient, and more productive mines. This in the face of a decline in ore grades, situated deeper, in challenging geographies and settings. Some miners are making very long-term investments in the management of future closure costs through careful planning and execution designed to protect the balance sheet. However as demonstrated by the recent Brumadinho tailings dam failure in Brazil, even partially “closed” facilities pose significant risk. This shows us that planning and properly executing closure measures during operations as a life-of-mine process is imperative if we are to sustain the industry and provide ongoing support of the communities where we operate. While operational innovations are receiving a great deal of attention to contain operating costs, the effort to keep a lid on the post-mining costs has not been as effective. However, there are exceptions and “integrated mine closure” is becoming more prevalent as a goal of industry. This paper explores the measures that need to be taken by mining companies to impose rigour on the closure planning and provisioning process, with the intention of both planning for closure, and in accounting for closure liabilities more effectively. This will be a dramatic departure from “free cash flow” optimisation, but may point the industry to a more sustainable future across its stakeholder base. Management Operating Systems (MOS) are well established in the mining industry, but are not typically applied to the discipline of closure planning. Currently closure planning is often overlooked within the shortterm planning and operational management decision-making processes. By linking people, process and technology in a systematic way that captures mine closure planning and integrating this into the MOS, particularly with life-of-mine planning, significant closure outcomes will be achieved, reflected in company value and ultimately sustaining the industry’s social licence to operate via a positive legacy.